Improving sample analysis and interpretation using QIAGEN's latest Investigator® STR multiplex PCR assays with a novel quality sensor. (December 2015) - Scherer, M.; König, M.; Breitbach, M.; Cornelius, S.; Bussmann, M.; Prochnow, A.; Peist, R.
Abstract: Novel STR Multiplex PCR assays addressing the European STR standard set (ESS) of loci as well as the new expanded CODIS core loci set have been developed. The Investigator 24plex QS and 24plex GO! Kits cover the expanded CODIS set and are designed for the amplification of purified DNA from casework and reference samples, or direct amplification of common database samples, respectively. The Investigator ESSplex SE QS Kit covers the ESS loci and SE33. All three kits have an internal performance control, the quality sensor (QS), included as component of the corresponding primer mixes. QS allows the user to monitor the performance of the PCR and to distinguish between inhibited and degraded samples.